Plasmonic Gratings in Optoelectronics and Fluorescence Enhancement - Amiri Naeini, Maryamossadat (Université d'Ottawa / University of Ottawa, 2025)
This thesis is an article-based report on the investigation and innovations which highlight the importance of plasmonic gratings in new device physics studies, fluorescence enhancement, and novel telecommunication chips. Plasmonic gratings are nanostructures created by periodically patterning a metal film with nanogrooves. These structures are capable of efficiently compensating the momentum mismatch between incident optical illumination and surface plasmon polariton (SPP) modes propagating along the metal film. Whilst a SPP mode is present on the film, one can benefit from their numerous advantageous features such as strong field enhancement in sub-diffraction-limit dimensions, and energetic hot carrier generation on the metal, to design new devices or study device physics. Plasmonic gratings can also perform as efficient structures in coupling the SPP modes on the surface to radiation channels. A metal-oxide-semiconductor (MOS) based high speed electro optic modulator is reported encompassing a plasmonic grating on the metal layer. The incident optical beam excites SPP mode on the MOS structure via plasmonic grating. Applying the electrical data as a drive voltage to the MOS structure, modifies the effective refractive index of SPP mode through carrier refraction effect in semiconductor layer (Silicon), thereby, modulating the coupling efficiency of incident beam to SPP mode. This provides an intensity modulated beam at the reflection. Numerical analysis, and experimental passive and active characterization of the device is reported. The 5 µm modulator works up to 22 GHz with 4 dB insertion loss and modulation depth of 2% over an optical bandwidth of 100 nm. The modulator offers an innovative solution for non-contact wafer-level testing - a critical and costly step in wafer manufacturing that presents challenges and creates a bottleneck in the transition to smaller technology nodes. The tunneling current in a similar MOS structure is measured and investigated theoretically. Studying the band diagram of the MOS device under accumulation and inversion regimes, shows that only Fowler-Nordheim tunneling is possible for the carriers transferring through the 5 nm thick Hafnium-dioxide (HfO₂) layer of the MOS structure. Theoretical modeling of the measured tunneling current shows a modified Fowler-Nordheim tunneling (MFN) law rules the dark current and photocurrent under inversion regime, fitting perfectly to the experimental results, and providing an opportunity to extract information such as the type and effective mass of the tunneling species, tunneling barrier height, and available population of carriers to initiate each tunneling process. A new tunneling channel of energetic holes created by SPPs on the metal surface is shown to be initiated from metal towards the semiconductor upon device illumination with an optical beam. Plasmonic silver gratings had been previously shown to create fluorescing carbon emitters from fabrication residues. In this thesis, the role of SPPs on a plasmonic grating to excite fluorophores strongly and enhance the fluorescence intensity by creating fast and competitive radiation channels, is investigated experimentally. SPPs propagating on the plasmonic grating can couple to the grating diffraction orders, resulting in highly directive radiation which is studied via numerical simulations. Available SPP modes near fluorophores, also reduce the emitters' lifetime through the Purcell factor. This phenomenon is theoretically modelled and emitters' lifetime on the plasmonic grating is measured experimentally. New fluorescence lifetime measurement method and plasmonic nanoantenna design for controlled localisation of fluorescence enhancement on a periodic structure surface is suggested as possible future research paths.
Keywords: Plasmonic Grating; Optical Telecommunication; Electro-optic Modulator; Tunneling; MOS device; Fluorescence; Lifetime; Carbon Dot